EFFECT SERVICE QUALITY AND CUSTOMER VALUE TO CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION USE OF DAMRI TRANSPORTATION MODE IN BANDUNG - Dadang Mohamad; Grida Saktian Laksito; Sukono Sukono (MEDIA STATISTIKA, 2022)
This study aims to determine how the influence of service quality and customer value on customer loyalty through customer satisfaction on DAMRI Transport Mode in Bandung, The research method used is quantitative, the sampling technique uses non-probability sampling and a sample of 260 respondents is obtained, the analytical tool used is Path Analysis and hypotheses using a significance test using the SPSS Version 24 and SEM AMOS analysis tool. The results of this study indicate that direct testing for direct testing of the customer loyalty variable it is found that service quality and customer satisfaction to customer loyalty has a positive and significant effect for use bus DAMRI in Bandung, while for customer value it has no effect on customer loyalty for use bus DAMRI in Bandung. With regard to customers' ownership, it is possible to increase the quality of service quality and customer loyalty to customers by giving goods a consumer satisfaction that would allow them to be loyal to using DAMRI bus as a mode of transportation in everyday activities.